Chiral inversion of drugs: coincidence or principle? - Wsól, V; Skálová, L; Szotáková, B (Current drug metabolism, 2004)
2-arylpropionic acid derivatives are probably the most frequently cited drugs exhibiting the phenomenon that is best known as chiral inversion. One enantiomer of drug is converted into its antipode either in the presence of a solvent or more often in inner environment of an organism. Mechanistic studies of the metabolic chiral inversion were carried out for several drugs from NSAIDs, and a model of this inversion was suggested and subsequently confirmed. The chiral inversion of NSAIDs has been intensively studied in the context of the pharmacological and toxicological consequences. However, the group of NSAIDs is not the sole group of drugs in which the inversion phenomenon can be observed. There exist several other drugs that also display chiral inversion of one or even both of their enantiomers. These drugs belong to different pharmacotherapeutic groups as monoamine oxidase inhibitors, antiepileptic drugs, drugs used in the treatment of hyperlipoproteinemia or drugs that are effective in the treatment of leprosy. Moreover, some chiral or prochiral drugs are metabolized to give chiral metabolites that undergo chiral inversion too, which can have direct impact on pharmacological properties or toxicity of the drug. As the process of chiral inversion is affected by several factors, so the intensity of chiral inversion of individual substances and at different conditions can differ considerably. Interspecies differences and types of tissue are reported to be the main factors that were recognized to play the key role in the process of chiral inversion. Some of more recent studies have revealed that several other factors, such as the route of administration or interaction with other xenobiotics, can influence the enantiomeric conversion, too. Chiral inversion does not seem to be a phenomenon connected with only several drugs from some unique group of 2-arylpropionic acid derivatives: it is also observed in drugs with rather different chemical structures and is much more frequent than it can be realized.
Keywords: molekulární konformace; tkáňová distribuce; Tissue Distribution; léčivé přípravky; druhová specificita; Molecular Conformation; stereoizomerie; Pharmaceutical Preparations; Animals; lidé; Stereoisomerism; Humans; zvířata; Species Specificity